In vitro elimination of gaseous microemboli utilizing hypobaric oxygenation in the Terumo® FX15 oxygenator. (October 2016) - Clingan, Sean; Schuldes, Matthew; Francis, Stephen; Hoerr, Harry; Riley, Jeff
Background: This study examines the efficacy of hypobaric oxygenation as it relates to the elimination of gaseous microemboli (GME) at designated flow, pressure and temperature combinations. Methods: Hypobaric oxygenation was employed for experimental trials (n=60), but not for control trials (n=60), while circuit design, data measurements and testing conditions were maintained for both settings. Hypobaric oxygenation conditions were created by applying 100% oxygen at sub-atmospheric sweep gas pressures of 0.67 atmospheres to the gas phase of an integrated hollow-fiber microporous membrane oxygenator. GME were quantified using an Emboli Detection and Classification system (EDAC), while a continuous air infusion, at a rate of 100 ml/min, was applied to the circuit. Trials were conducted at 37°C, 28°C, and 18°C and at two flow and line pressure combinations of: 3.5 L/min & 150 mmHg and 5 L/min & 200 mmHg. Results: Sub-atmospheric sweep gas pressures allowed adequate oxygenation independent of carbon dioxide removal while significantly reducing the potential entrance of nitrogen into the blood. GME was reduced significantly across all temperatures and flows when compared to control trials; GME counts were reduced by 99.7% post-oxygenator and 99.99% at the arterial cannula. Conclusion: Correlation between the use of hypobaric oxygenation and GME counts suggests hypobaric oxygenation could play a significant role in the reduction of GME.